Isogeometric Analysis with Trimmed CAD Models. Issue 1 (17th December 2018) - Marussig, Benjamin
Abstract: Trimmed CAD models are the most popular geometry representation in engineering design, but their direct application to an isogeometric analysis can lead to ill‐conditioned system matrices. An approach is presented that effectively resolves this issue by combining so‐called extended B‐splines with a local refinement procedure.